A flexible conductive hybrid elastomer for high-precision stress/strain and humidity detection. Issue 1 (January 2019) - Liu, Haoran; Zhang, Zhenyi; Ge, Jun; Lin, Xiao; Ni, Xinye; Yang, Huilin; Yang, Lei
Abstract: Flexible and environment-responsive materials are essential for a large number of applications from artificial skin to wearable devices. The present study develops a flexible, ultra-low cost conductive hybrid elastomer (CHE), which possesses high responsive capabilities to stress/strain and humidity. CHE was composed of polydimethylsiloxane (PDMS) and starch hydrogel (SH), enabling great elasticity (56 kPa), high conductivity (10 −2 S/m) and high sensitivity to external stimuli (gauge factor of CHE under stress and strain are 0.71 and 2.22, respectively, and sensitivity to humidity is 1.2 × 10 −6 S/m per RH%). These properties render CHE a promising candidate for artificial skin and wearable electronics applications of continuously monitoring environmental information.